(untitled) (Journal of Science and Technology, 2016)
The objective of this paper was to investigate the various dimensions of basic school dropouts in rural Ghana using the Asutifi district as a case study. The analysis of data (both quantitative and qualitative) gathered from several stakeholders of basic education in the district, revealed that the causes of school dropout were rather complex. Poor educational outcomes in terms of per- formance of candidates in the final examinations of the basic level as a result of the poor quality of teaching and learning in the rural environment was directly linked to the high rate of drop- out. Although some stakeholders claimed that poverty was the main cause of school dropout, the significance of the loss of confidence in the educational system cannot be overemphasised. The policy implication is that quality consideration in the basic education delivery should now be the priority in order to regain the confidence of parents and their wards in the educational system in general so that enrolments and retention of children in school could be enhanced.